La organización social en la ciudadela Brisas del mar de la ciudad de Machala, 2013 - Arredondo Poma, Francisco Javier (2014)
In the present research is to demonstrate the characteristics of the development of the activities and processes of management of a neighborhood organization, within which we see a complex system of socioeconomic relations that determine the quality of life of the inhabitants of the citadels "The Brisas "city of Machala, province of El Oro. the city and effects that the activities of the barrel leadership, becoming axes of the proposal to improve the quality of life of citizens who are at a disadvantage arises for its operational security efforts, grooming your sector control alcohol or prohibited substances, for procedures on your needs, the inhabitants obtained from the same to get answers that help improve their quality of life dependent on social management their representatives.